2021
DOI: 10.1007/s11295-021-01515-w
|View full text |Cite
|
Sign up to set email alerts
|

Many candidates for a single chair: a critical review of the genetic determinant of flat fruit shape trait in peach (Prunus persica L. Batsch)

Abstract: Known since ancient times, flat-shaped peach (Prunus persica L. Batsch) fruits have aroused considerable research interest. Breeding activities for this trait have expanded since the 1980s of the last century in several countries, in parallel with research into its genetic basis. Following the need for molecular markers to assist selection, linkage mapping studies have positioned the flat shape S locus at the end of chromosome 6. Recently, a series of independent studies focused on detailed characterization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The protein and RNA profiles have suggested that OVATE is a novel class of proteins named as OFPs (ovate family proteins) ( Liu et al, 2002 ). Owing to their effects on fruits, OFPs have been studied in many fruit crops, and the results have indicated that OFPs have great influence on a variety of aspects in plants, including fruit shape ( Liu et al, 2002 ; Tsaballa et al, 2011 ; Cirilli and Rossini, 2021 ; Han et al, 2022 ), tuberous root shape ( Wang et al, 2020 ), ovule development ( Pagnussat et al, 2007 ), secondary cell wall formation ( Li et al, 2011 ; Wang et al, 2011 ), vasculature development ( Schmitz et al, 2015 ), fruit ripening ( Liu et al, 2015b ), DNA repair ( Wang et al, 2010 ), floral organs, compound leaf and silique ( Liu et al, 2002 ; Wang et al, 2011 ). Here, we briefly summarized the functions of OFPs in Arabidopsis and some common crops ( Figure 8A ), and we believe that more functions of OFPs will be gradually detected in plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein and RNA profiles have suggested that OVATE is a novel class of proteins named as OFPs (ovate family proteins) ( Liu et al, 2002 ). Owing to their effects on fruits, OFPs have been studied in many fruit crops, and the results have indicated that OFPs have great influence on a variety of aspects in plants, including fruit shape ( Liu et al, 2002 ; Tsaballa et al, 2011 ; Cirilli and Rossini, 2021 ; Han et al, 2022 ), tuberous root shape ( Wang et al, 2020 ), ovule development ( Pagnussat et al, 2007 ), secondary cell wall formation ( Li et al, 2011 ; Wang et al, 2011 ), vasculature development ( Schmitz et al, 2015 ), fruit ripening ( Liu et al, 2015b ), DNA repair ( Wang et al, 2010 ), floral organs, compound leaf and silique ( Liu et al, 2002 ; Wang et al, 2011 ). Here, we briefly summarized the functions of OFPs in Arabidopsis and some common crops ( Figure 8A ), and we believe that more functions of OFPs will be gradually detected in plants.…”
Section: Discussionmentioning
confidence: 99%
“…In radish (Raphanus sativus), RsOFP2.3 is negatively associated with tuberous root elongation and the tuberous root shape (Wang et al, 2020). In peach (Prunus persica), PpOFP1 regulates fruit shape (Cirilli and Rossini, 2021), and another similar study showed that PpOFP1 physically interacts with a ZF-HD_dimer domain protein PpZFHD1 and regulates the salt tolerance of tomato (Tan et al, 2021). In cotton (Gossypium hirsutum), GhOFP4 was found to regulate fiber development (Gong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ovate Family Proteins (OFPs) were first discovered in Solanum lycopersicum L. (Tomato) over a century ago and were first cloned in 2002 [4,5]. In the original studies, OFPs were found to have a crucial role in determining the pear-type elongated shape of tomato and peach fruit [6,7]. They reside in a conserved OVATE domain of 70 amino acid residues in length.…”
Section: Introductionmentioning
confidence: 99%
“…Oryza sativa also shows the aforementioned BELL-KNOX TALE suppression mediated by OsOFP02 along with the control of leaf and seed shape, plant height, the vascularity of stems, and biosynthesis of lignin [16]. The regulation of fruit shape in Prunus persica (Peach) is mediated by PpOFP1 [7]. Moreover, MaOFP01 is involved in fruit ripening in Musa paradisiaca (Banana), CmOFP13 in the fruit shape Cucumis melo (Melon), CsOFP12-16c in the silique development of Cucumis sativus (Cucumber), CaOFP01 and CaOFP20 in the fruit shape and length of Capsicum annuum (Sweet And chili pepper), and lastly GhOFP04 in the fiber development of Gossypium hirsutum (Cotton) [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analysis of peach fruit shape mainly focused on the Mendelian flat trait controlled by the dominant S locus initially described by Lesley 9 and fine-mapped to the distal part of chromosome 6 10 , 11 , 12 , 13 . Apart from this locus, knowledge of other genetic factors contributing to shape variation in non-flat-type fruits is still limited.…”
Section: Introductionmentioning
confidence: 99%